Pengembangan Framework Yii Dalam Pembangunan Sistem Inventaris STMIK Prabumulih Dengan Konsep User Centered Design (UCD) - Ariansyah Ariansyah; Ahmat Josi (Politeknik Harapan Bersama, 2018)
STMIK Prabumulih is a college that has two departments, namely the department of the information system level of education (S1) and computerized accounting level of diploma three (D3). STMIK Prabumulih has a vision of